Ionic conductivity investigation in lanthanum (La) and strontium (Sr) co-doped ceria system 41953 - Jaiswal N.; Upadhyay S.; Kumar D.; Parkash O. (My University, 2025)
Effect of strontium doping on ionic conductivity of lanthanum-doped ceria has been investigated. Distribution and average radius of oxygen vacancies formed from divalent and trivalent dopant cations in co-doped system has been calculated using hard-sphere model. Phase identification, microstructure and ionic conductivities of samples have been studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), and AC impedance spectroscopy, respectively. X-ray diffraction reveals that all the samples are single phase with cubic fluorite-type structure. Dense ceramics with density w95% of the theoretical density have been obtained without using any sintering aid. The results show that the samples co-doped with La and Sr exhibit higher ionic conductivity and lower activation energy than those of ceria doped with La only in the intermediate temperature range. The highest ionic conductivity has been observed for Ce0.89La0.07Sr0.04O1.925 in the samples investigated (4.01 × 10~3 S cm-1) at 500 °C, which is 20 times as high as that of Ce0.85La 0.15O1.925. Concept of average oxygen vacancy radius has been found to be a useful in calculating the lattice parameter in this system. © 2012 Elsevier B.V. All rights reserved.